Perioperative Prophylactic Antibiotics in 1, 250 Orbital Surgeries. Issue 4 (July 2020) - Fay, Aaron; Nallasamy, Nambi; Allen, Richard C.; Bernardini, Francesco P.; Bilyk, Jurij R.; Cockerham, Kimberly; Cruz, Antonio Augusto; Devoto, Martin; Dolman, Peter J.; Dutton, Jonathan J.; Jordan, David R.; Kersten, Robert; et al.
Abstract : Purpose: Intravenous antibiotic prophylaxis is used for many clean-contaminated surgeries or clean surgeries with an implant, but its value for clean orbital surgery has not been determined. This study investigated infection risks and adverse effects related to antibiotics in patients undergoing orbital surgery. Methods: A prospective, nonrandomized comparative case series of all patients undergoing orbital surgery with participating surgeons between October 1, 2013, and March 1, 2015. Types of surgery, antibiotic regimens, corticosteroid use, antibiotic side effects, and surgical site infections (SSIs) were entered into an electronic database and subsequently analyzed. Cases in which patients received postoperative oral antibiotics were analyzed separately. Results: Of 1, 250 consecutive orbital surgeries, 1, 225 met inclusion criteria. A total of 1208 patients were included in the primary analysis: 603 received no antibiotic prophylaxis (group A), and 605 received a single dose of intravenous antibiotic (group B). Five patients (0.42%) developed an SSI, 3 in group A and 2 in group B. The difference in SSI rates was not statistically significant between the 2 groups ( p = 0.66). Antibiotic prophylaxis, alloplastic implants, paranasal sinus entry, and corticosteroid use were not associated with differences in SSI rates. All SSIs resolved on a single course of oral antibiotics; an implant was removed in 1 case. There were no complications associated with a single dose of intravenous prophylaxis. However, 12% of 17 patients (group C) who received 1 week of oral postoperative prophylactic antibiotics developed antibiotic-related complications (diarrhea, renal injury), yielding a number needed to harm of 8.5. Conclusions: In this large series, antibiotic prophylaxis does not appear to have reduced the already low incidence of SSI following orbital surgery. Given the detriments of systemic antibiotics, the rarity of infections related to orbital surgery, and the efficacy of treating such infections should they occur, patients undergoing orbital surgery should be educated to the early symptoms of postoperative infection and followed closely, but do not routinely require perioperative antibiotics. Abstract : Perioperative antibiotics do not appear to decrease the already low incidence of surgical site infection in patients undergoing orbital surgery.